The Embedded Market and Ideology Critique - Johnson, Pauline (Critical Horizons, 2011)
The article examines the ideology critical potentials of the concept of the embedded market, made famous by philosopher and economic historian Karl Polanyi. It explores several readings of this concept and assesses their ability to revive critical powers of sociology. It discusses the book "The New Spirit of Capitalism," by Luc Boltanski and Eve Chiapello, as a specific take on such an idea. It also offers a re-examination of Polanyi's interpretations of the embedded markets thesis.
Sociology; Philosophy
Keywords: Boltanski and Chiapello; embedded markets; ideology; neoliberalism; philosophers; philosophy; social theory; sociology

Work and Neoliberal Globalization: A Polanyian Synthesis - Bandelj, Nina; Shorette, Kristen; Sowers, Elizabeth (Sociology Compass, 2011)
This article reviews sociological research about economic globalization’s impact on work and labor in developed and developing countries since the 1980s. We find that this period of neoliberal globalization influences work because of intensified activities of multinational corporations (MNCs), financialization of the global economy, and amplified prominence of international organizations, some of which diffuse neoliberal policy scripts while others mobilize a transnational civil society. Research we review generally points to liabilities of neoliberal globalization for workers. To understand these findings, we apply Karl Polanyi’s concepts of fictitious commodities, the self-regulating market, and the double movement. We propose that, on the one hand, the activities of MNCs, international financial organizations, and many states exemplify pushes for institutional separation of economy and society in effort to institutionalize the idea of a self-regulating market at a global scale, which increases labor commodification and global inequalities. On the other hand, the activities of social movements, including unions and transnational actors that target globalization’s impact on work, constitute the counter movement at national and global levels resisting marketization and pushing for labor decommodification. The aftermath of the ongoing economic crisis will tell to what extent this countermovement will be successful in generating an alternative to neoliberal globalization, and more protections for workers.
Sociology
Keywords: double movement; fictitious commodities; globalization; neoliberalism; self-regulating market

Contracts in the English NHS: Market levers and social embeddedness - Hughes, David; Petsoulas, Christina; Allen, Pauline; Doheny, Shane; Vincent-Jones, Peter (Health Sociology Review, 2011)
This paper draws parallels between the market trend in the English NHS and Polanyi's (1957) The Great Transformation account of how the rise of markets provokes a self-protective counter-reaction that tries to re-embed economic relations in social relations. We report findings from a qualitative study of NHS contracting, which examines the recent move to harder-edged contracts with greater use of financial penalties and incentives. In practice, use of these techniques tended to be confined to nationally-mandated sections of the contract rather than emerging from local bilateral agreements, and when things went wrong the parties relied more on cooperative behaviour than on the provisions of the contract to find solutions. Making the current contracting system work depended more on existing relational networks than on the incentive structures created by recent 'marketisation' initiatives, but the inability of the market to evolve as expected has encouraged policy makers to publish plans for further radical reforms.
Sociology
Keywords: England; English NHS; NHS reforms; competition (economics); contracting; contracting out; cooperativeness; decentralization in management; financing of research; government agencies; health sociology; incentives in industry; information storage & retrieval systems - medical care; institutional cooperation; interviewing; marketisation; meetings; methodology; national health services; negotiation; organizational effectiveness - evaluation; organizational structure; organizational change; pay for performance; purchaser/provider relations; qualitative research; research methodology; risk management in business; secondary analysis; social context; sociology; theory

The Commodification of Pollution and a Preemptive Double Movement in Environmental Governance: The Case of Water Quality Trading - Mariola, Matt J. (Organization & Environment, 2011)
The management of environmental pollution has traditionally been accomplished via the regulatory power of the state, but more recently the rise of a new, market-based form of governance has been observed. This article examines the sector of water quality trading, in which caps are placed on surface water pollution and polluters can purchase “offset credits” from farms or other polluters who are under their cap. Using a content analysis of program case studies and federal and state trading rules, the author analyzes this emergent form of environmental governance using an expanded Polanyian framework that he terms the preemptive double movement. Instead of the state reacting to the dangers of a new market form after the fact, here the state uses its existing authority to constrain the market so that further environmental damage does not result. The author describes eight specific regulatory mechanisms that illustrate this preemptive double movement at work.
Sociology; Anthropology; Environmental Studies
Keywords: Polanyi; business & the environment; commodification; double movement; ecological impact; nutrient trading; pollution; water quality management; water quality trading

Grounding Globalization: Labour in the Age of Insecurity - Webster, Edward; Lambert, Rob; Beziudenhout, Andries (John Wiley & Sons, 2011)
*Winner of the 2009 Distinguished Scholarly Monograph Prize, awarded by the American Sociological Association Labor and Labor Movements section* Claims have been made on the emergence of a new labour internationalism in response to the growing insecurity created by globalization. However, when persons face conditions of insecurity they often turn inwards. The book contains a warning and a sign of hope. Some workers become fatalistic, even xenophobic. Others are attempting to globalize their own struggles. Examines the claim that a new labour internationalism is emerging by grounding the book in evidence, rather than assertion Analyzes three distinct places – Orange, Australia; Changwon, South Korea; and Ezakheni, South Africa – and how they dealt with manufacturing plants undergoing restructuring Explores worker responses to rising levels of insecurity and examines preconditions for the emergence of counter-movements to such insecurities Highlights the significance of 'place' and 'scale', and demonstrates how the restructuring of multi-national corporations, and worker responses to this, connect the two concepts
Sociology; Geography
Keywords: Polanyi problem; critique; globalization; internationalism; labour; science / earth sciences / geography

Karl Polanyi: The Limits of the Market - Barnes, Tom (Journal of Australian Political Economy, 2011)
The article reviews the book "Karl Polanyi: The Limits of the Market," by Gareth Dale.
Keywords: DALE; Gareth; KARL Polanyi: The Limits of the Market (Book); Polanyi; Karl; 1886-1964

Embedding Economic Relationships through Social Learning? The Limits of Patient and Public Involvement in Healthcare Governance in England - Vincent-Jones, Peter (Journal of Law & Society, 2011)
The strategy for NHS modernization in England is privileging individual choice over collective voice in the governance of healthcare. This paper explores the tension between economic and democratic strands in the current reform agenda, drawing on sociological conceptions of embeddedness and on theories of reflexive governance. Building on a Polanyian account of the disembedding effects of the increasing commercialization of health services, we consider the prospects for re-embedding economic relationships in this field. An analysis is provided of the limits of the present legal and regulatory framework of Patient and Public Involvement (PPI) in establishing the democratic and pragmatist conditions of social learning necessary for effective embedding. We show how the attainment of reflexive governance in the public interest is dependent on such conditions, and on the capacities of patients and the public to contribute to debate and deliberation in decision making, including on fundamental policy questions such as how services are provided and by whom.
Law; Sociology
Keywords: Great Britain; National Health Service; disembeddedness; embeddedness; medical care; public interest; social learning

Le concept de « marchandise fictive », pierre angulaire de l'institutionnalisme de Karl Polanyi ? - Postel, Nicolas; Sobel, Richard (Revue de philosophie économique, 2011)
The notion of “fictitious commodities” is not simply a convenient heterodox slogan to criticize the radical limits of any trade system and the analytical limits of the dominant theory. It is rather the foundation of the institutional perspectives that underlie all Karl Polanyi’s sociohistoric analyses. This article explains and articulates both the theoretical level using the institutional approach to commodities and a philosophical level using a broad definition of the economy. There is, however, a limit to the notion of the institution, which connects both levels: it is not articulated practically such that the potential and critique of this construct may be weakened.
Sociology; Economics
Keywords: capitalisme; institution; marchandises fictives; raison pratique; économie substantive

Would You Barter with God? Why Holy Debts and Not Profane Markets Created Money - Semenova, Alla (American Journal of Economics and Sociology, 2011)
Attempting to revitalize the substantive approach to economics in the tradition of K. Polanyi, this paper revives the neglected substantive theory of money's origins by Bernhard Laum and thus disputes the formal approaches that see the origins of money in the context of trade. A wide range of evidence, from archeological to etymological, is utilized to demonstrate that relations between men and God, carried out through the intermediary of state-religious authorities, played a causal role in the genesis of the ox-unit of value and account, and, further, in the origins of money, and, subsequently, coinage. The substantive state-religious approach presented in this paper is also compared and contrasted to the Chartalist perspective on money's origins. It is concluded that the substantive approach presented in this paper differs from the more formal approaches (e.g., Metallism) because it does not rely upon a projection of modern institutions and habits of thought (e.g., a medium of exchange; monetary taxation) into ancient societies.
Economics; Sociology
Keywords: ancient societies; money; substantive approach

Lineages of Embeddedness: On the Antecedents and Successors of a Polanyian Concept - Dale, Gareth (American Journal of Economics & Sociology, 2011)
Since the 1980s, much debate has revolved around Karl Polanyi's concept of the 'dis/embedded economy,' generating some light and not a little heat. This paper looks at three reasons that account for part of the 'heat.' It begins by tracing the sources upon which Polanyi drew. They include Karl Marx, Ferdinand Tönnies, and Max Weber, along with anthropology of the inter-war period, and German and American Institutionalist economics. After exploring the differing ways in which these varying currents conceptualize the relationship between economy and society, I explore the different interpretations of what Polanyi means by embeddedness, and the different purposes to which contemporary economic sociologists have put the term. For some, he is held up as the originator of a line of sociological analysis that treats 'the economy' as a subsystem 'embedded in' a social system. In this reading the emphasis is upon the moral underpinnings of market behavior, in contrast to the naturalism of Ricardo, Malthus and their heirs. For others, his 'disembedding' thesis contains a more radical tale: of the market economy coming to dominate 'society,' bringing forth a sorcerer's apprentice world of untrammeled market forces that, although human creations, lie beyond conscious human control.
Political Science; Sociology
Keywords: MARX; Karl; 1818-1883; POLANYI; Karl; 1886-1964; TONNIES; Ferdinand; 1855-1936; WEBER; Max; 1864-1920; economic philosophy; economics; embeddedness; influence (psychology); intellectual life - history; socioeconomics

Another ‘Great Transformation’ or Common Ruin? - Smart, Barry (Theory, Culture & Society, 2011)
In the aftermath of the 1930s Great Depression, and as the Second World War was drawing to a close, Karl Polanyi concluded a critical analysis of market capitalism on an optimistic — and with the benefit of hindsight we can add premature — note, remarking that the ‘primacy of society’ over the economic system had been ‘secured’. Eighty years later, amidst the unresolved turmoil of another comparable global capitalist economic crisis and accumulating signs of a growing environmental crisis, both a direct legacy of the operation of the ‘market economy’, the remedy advocated by governments and policy-makers is effectively a return to ‘business as usual’. Notwithstanding various manifestations of public expression of dissatisfaction with the consequences of global ‘free-market’ capitalism, which include increasing inequality, poverty, unemployment, depletion of scarce natural resources, environmental destruction, pollution and waste, the default policy setting remains to restore global economic growth, to generate further increases in production and cultivate ever-rising rates of consumption, even if the risk is ‘common ruin’. However, there are a number of realistic, progressive and radical alternatives proposed by critical analysts, including a political program for ‘de-growth’ , a reinvention of communism and detailed policy proposals outlining the measures necessary to promote a transition to a ‘post-capitalist’ society with a sustainable economy.
Sociology
Keywords: BAUMAN; Zygmunt; Farewell to Growth (Book); First As Tragedy; Then As Farce (Book); LATOUCHE; Serge; Living on Borrowed Time: Conversations With Citlali Rovirosa-Madrazo (Book); ZIZEK; Slavoj; 1949-; capitalism; communist hypothesis; de-growth; degrowth; economic growth; environment; financial crisis; nonfiction; sustainability

Positivism and 'Functional Theory' in the Thought of Karl Polanyi, 1907-1922 - Dale, Gareth (Sociology Compass, 2011)
Karl Polanyi is the author of a modern social science classic, The Great Transformation, as well as a number of well-known and widely debated essays collected in Trade and Market in the Early Empires and Primitive, Archaic and Modern Economies. These texts were researched and written either during his second exile in 1930s Britain or in wartime or post-war North America. Not so well known, however, are his Hungarian writings from the 1910s. Until recently, very few of these had been republished or translated, although this is in the process of being rectified [: Karl Polanyi: The Hungarian Writings]. With reference to new translations of his Hungarian writings, to interviews with his daughter, Kari Polanyi-Levitt, as well as to biographical essays by György Litván, Évá Gábor, Endre Kiss, and Zoltán Horváth, this article explores his early influences, drawing attention in particular to his flirtation with and then violent reaction against philosophical materialism and 'objectivist' sociology, his appreciation of Ernst Mach's positivism, and his adherence to the 'functional theory' of contemporary Guild Socialism.
Political Science; Sociology
Keywords: positivism; religion; social sciences; socialism

Crisis and renewal: the outlines of a twenty-first century new deal - Block, Fred (Socio-Economic Review, 2011)
Most analyses of the US financial crisis of 2007–2009 focus on the proximate causes. This article sees the crisis as a consequence of the decline of a long-term pattern of accumulation in the USA and seeks to outline the requirements for a new period of dynamic economic growth. Drawing on work done by the French Regulation theorists and the US analysts of Social Structures of Accumulation, the paper attempts to describe the types of institutional changes that would be needed to spark a new period of stable economic growth in the USA and in the rest of the world economy. The paper outlines what a green mass consumption economy might involve.
Sociology
Keywords: United States; capitalism; capitalist systems; crises; economic change; economic reform; financial crisis; green economy; institutional change

NAFTA and Gatekeeper: A Theoretical Assessment of Border Enforcement in the Era of the Neoliberal State - Ackerman, Edwin (Berkeley Journal of Sociology, 2011)
The coexistence of border-enforcement policies such as Operation Gatekeeper and economic liberalization programs such as NAFTA is arguably paradoxical given the simultaneous push towards afree flow of products but curtailed flow of labor. This paper presents a critical review and reassement of existing accounts of neoliberal statehood to make sense of this apparent puzzle. While some have argued that the state is eroding under neoliberal globalization, a more sophisticated analysis has focused on how it has been transformed. David Harvey and LoIc Wacquant focus on the role of the repressive apparatus in upholding neoliberalism. Building on Harvey and Wacquant, and returning to Karl Polanyi, I emphasize the ways in which the state has tried to make use of a repressive apparatus as a claim to social protection a function that becomes necessary as the state advances liberalization. The coexistence of NAFTA and Gatekeeper should be not be understood as an anomaly but rather as an expected feature of contemporary statehood.
Sociology
Keywords: North American Free Trade Agreement (NAFTA); United States; border security; finance; free trade; liberalization; neoliberalism; social protection

On the Nation-Specific Features of Modernization in Russia - Yadov, Vladimir (Social Sciences, 2011)
The article offers information on the features that contribute to the modernization in Russia. It discusses various value structure theories from various persons. It says that from the analysis of world survey statistics, Yevgeny Yasin concluded that Russians are more conservative compared to other western countries. Details regarding the mentality of Russian people are discussed including Russians' high score on cycloid scale and their tendency to fulfill their task at the last moment. Moreover, it says that Russia's activist theories, Karl Polanyi and Douglas North's path dependence theory, and the global world system theory as a new phase to human civilization's history are important features to the country's modernization.
Sociology
Keywords: Russia; Russia - social conditions; YASIN; Yevgeny; economic development; modernization (social science); modernization theory; nation-state; national interest; social development theory

After Neoliberalism - Antonio, Robert J. (The Wiley-Blackwell Companion to Sociology, 2011)
This chapter contains sections titled: * Clashing Models of Capitalism: Hayek VS. Polanyi * Market Liberalism's Return: From the “Not Quite Golden Age” to the “Great U - Turn” * Hegemonic Neoliberalism: From Crest to Crisis to Emphatic Reassertion(?) * Capitalism at the Point of Inflection: Neoliberalism's Wake * Conclusion * References
Sociology
Keywords: 2008 financial meltdown; HAYEK; Friedrich A. von (Friedrich August); 1899-1992; Hayek's and Polanyi's classic texts; New Deal; The Great U-Turn; ascendant neoliberalism; cutting edge issues; great recession; hegemonic culture; neoliberalism; neoliberalism's wake; self-regulating market

Il sofisma economicista: intorno a Karl Polanyi - Caillé, Alain (sn, 2011)
KM translate: "The economic sophistry" and "The two meanings of" economic "", short writings by Karl Polanyi published here partially in a version taken from the French magazine MAUSS, represent a wonderful example of critical synthesis and set of depth of analysis, an analysis that comes to the conviction of the anthropological and social disaster caused not only by liberalism, but even more by the fallacy of an entire system of thought, economic science, which seeks to justify and support it. In support of the interesting pages of Polanyi, this book presents two contributions, respectively by Alain Caillé with Jean-Louis Laville and Jerome Maucourant, which, in addition to quickly presenting the intellectual biography of the Hungarian philosopher, clarify the extreme relevance of his critique of capitalism and the society of the markets. Polanyi emerges as an economist from the solid historical and anthropological foundations that, with his work, has been able to dismantle the apparently solid building of the classical economy to reveal its deceptive essence: that of a vast theoretical apparatus that attributes universal validity to a precise historical contingency, the liberal laissez-faire of nineteenth-century Europe. It is urgent - and this task the present publication intends to offer an agile contribution - rediscovering and actualizing the figure of Karl Polanyi, atypical but central in the intellectual panorama of the twentieth century. building apparently balance of the classical economy to unveil its deceptive essence: that of a vast theoretical apparatus that attributes universal validity to a precise historical contingency, the liberal laissez-faire of nineteenth-century Europe. It is urgent - and this task the present publication intends to offer an agile contribution - rediscovering and actualizing the figure of Karl Polanyi, atypical but central in the intellectual panorama of the twentieth century. building apparently balance of the classical economy to unveil its deceptive essence: that of a vast theoretical apparatus that attributes universal validity to a precise historical contingency, the liberal laissez-faire of nineteenth-century Europe. It is urgent - and this task the present publication intends to offer an agile contribution - rediscovering and actualizing the figure of Karl Polanyi, atypical but central in the intellectual panorama of the twentieth century.
Sociology
Keywords: business & economics; economic theory

Polanyi on Markets, Democracy and the Crisis of Liberalism - Ebner, Alexander (The Beginnings of Scholarly Economic Journalism, 2011)
Karl Polanyi, who was born in 1886 in Vienna and died in 1964 in Pickering, Ontario remains a most influential theoretical figure in the social sciences, in particular stimulating both analytical and policy-related concerns that are related with the new institutionalism in economics, sociology and political science. Polanyian insights on the political economy of economic development from an institutional perspective have persistently shaped a variety of discourses that range from the theory of the welfare state to research in comparative economic systems and economic anthropology. Polanyi’s “Great Transformation” may be singled out as a key contribution to both the domains of economic sociology and political economy, as it addresses basic tensions between the developmental dynamics of the market economy and the institutional substance of political democracy (Block 2001).
Sociology; Political Science
Keywords: crisis of liberalism; early writings; methodology; methodology of the social sciences

Karl Polanyi and the New Economic Sociology: Notes on the Concept of (Dis)Embeddedness - Machado, Nuno Miguel Cardoso (Social Science Research Network, 2011)
Within the context of the New Economic Sociology, Karl Polanyi is almost universally considered the "father" of the concept of embeddedness. However, this concept has been subject to selective appropriation by this discipline and its relationship to the remaining theoretical edifice constructed by Polanyi has been neglected. It is, in fact, possible to refer to the "great transformation" to which the concept of embeddedness has been subjected: whereas in Polanyi’s work it is associated with the macro(economic) level and is used as evidence of the exceptional nature of the capitalist market economy –- disembedded from society –- in NES, it is normally associated with the meso (and even micro) level, on the assumption that all economies –- including capitalist economies -– are embedded. in RCCS Annual Review, No. 3, pp. 119-140
Sociology
Keywords: Karl Polanyi; capitalism; embeddedness; market economy; new economic sociology

Avez-vous lu Polanyi ? - Maucourant, Jérôme (HAL, 2011)
"Cette étude présente le parcours intellectuel de Karl Polanyi (1886-1964), à la croisée de l'économie, de l'histoire et de la sociologie, et propose une synthèse de l'ensemble de son oeuvre." Postface accessible en ligne : [ http://www.contretemps.eu/lectures/bonnes-feuilles-avez-vous-lu-polanyi-j%C3%A9r%C3%B4me-maucourant-postface ]
Economics; Sociology
Keywords: Great Transformation; The (Book); La Grande Transformation; critique and interpretation; critique et interprétation; libéralisme; économie politique

Whither the Counter-Movement? Hayek, Polanyi, and the Politics of No Alternative - Mudge, Stephanie (Conference Papers – American Sociological Association, 2011)
This paper turns Karl Polanyi's concept of the "double movement" back on Polanyi and his intellectual contemporary, Friedrich Hayek, as a means to insight into the structural conditions of counter-movement in the second half of the 20th Century. After elaborating on the double movement concept, I contrast the trajectory of Polanyi and his greatest work, The Great Transformation, with that of Friedrich Hayek and his contemporaneous Road to Serfdom–treating each as protagonists in the movement/counter-movement system of relations that, for Polanyi, is the site of history's forward motion. Building on citation data, news articles, archival records and secondary sources, I argue that Polanyi's conditions of intellectual production–including a lack of economic allies in the capitalist West, professional instability, tenuous ties to academic economics, and a lifetime of financial insecurity–explain the ongoing quarantine of Transformation within the academic social sciences. These conditions of production contrast starkly with the Hayekian counterexample. Taken together, the analysis casts light on the ongoing hegemony of the "liberal creed" and the weakness of effective opposition: the trajectory of the two figures offers clues into how structures of intellectual production are linked to (or severed from) movement and counter-movement, offering insight into why, even in the face of financial crisis and significant public anger against the moneyed ranks of the financial sector, we continue to exist in a world of "no alternative".
Sociology
Keywords: HAYEK; Friedrich A. von (Friedrich August); 1899-1992; POLANYI; Karl; 1886-1964; capitalism; intellectuals; protagonists (persons)

Reading the Story of Law and Embeddesness through a Community Lens: A Polanyi-Meets-Cotterrell Economic Sociology of Law [article] - Perry-Kessaris, Amanda (Northern Ireland Legal Quarterly, 2011)
In this paper I propose that role of law in Karl Polanyi's concept of the 'always embedded economy' (Block 2003) can be enriched by the application of the lens of community (Perry-Kessaris 2008) developed by Roger Cotterrell (1996-present). I begin with Polanyi's suggestion that economic action and interaction are always 'embedded' in wider social life. Reading through the lens of community, we can be more specific: any actor is at once engaged, to different degrees (from fleeting to stable), in multiple types (whether focusing on instrumental, traditional, affective and/or belief-based action) of social life. I then explore a second, implicit, cornerstone of Polanyi's argument: that analytical and normative approaches to economy may become dis-embedded from wider social life. Reading through the lens of community we can again be more specific: In the transformation to a market society, the analytical and normative approaches that are central to economic actions and interactions are confused with, and privileged over, those that are central to non-economic actions and interactions. This confusion and privileging can have what we might call a performative effect on action and interaction. Finally, I explore Polanyi's story of law as a facilitator both of dis-embedding movements and of re-embedding counter-movements. The application of a law-and-community lens suggests some additional details of that storyline and that there are additional plotlines to be pursued. The practical potential of this Polanyi-meets-Cotterrell economic sociology of law is briefly illustrated with references to two 21st Century cautionary tales: the World Bank's investment climate programme and the 2008 financial crisis.
Law; Sociology
Keywords: COTTERRELL; Roger; United Kingdom; economic sociology of law; embeddedness; investment climate; law and community

Polanyi contre Freeman. (Polanyi against Freeman. With English summary.) - Postel, Nicolas; Sobel, Richard (Revue de la Regulation, 2011)
The dominant approach of CSR is based on the concept of "stakeholders" (R. E. Freeman). More than a theory, it is a slogan which irrigates as much the scientific discourse as the manager and political discourses. We can make two readings of this slogan. The first one, which is very reducing for us, consists on the deconstruction of the firm as institution and its replacement by a market representation based on bilateral exchanges between rational individuals. The second one, more promising in order to identify the potentialities of CSR in terms of regulation, intends to found the notion of stakeholder on a theory of actor and institution. It is the position which we defend by mobilizing Karl Polanyi's institutionalism.
Sociology; Economics
Keywords: Marxian; Sraffian; business objectives of the firm; corporate culture; current heterodox approaches: institutional; current heterodox approaches: socialist; diversity; evolutionary; social responsibility

Double Movements of Destruction and Regulation: Commodity Chains and a New Political Economy of the Environment - Roberts, J.; Carmin, JoAnn; Rudel, Thomas (Conference Papers – American Sociological Association, 2011)
Sociologists have examined the ways in which capitalism contributes to environmental degradation as well as how, in selected circumstances, it increases efficiency while reducing pollution and human injustices. In this review, we draw on Polanyi's concept of the double movement to illustrate how self regulating markets give rise to environmental degradation and inequities and, in response, how these conditions often stimulate the emergence of collective action in pursuit of regulatory and social reforms. This process is iterative, with capitalist initiated degradation of the environment followed by regulatory reform and then efforts to weaken the regulatory regimes. We illustrate how resource extraction contributes to environmental degradation and power inequalities, pollution from industrial production is unequally distributed among workers and communities, and how the desire to limit exposure to risk has opened new markets and led to policies that contribute to consumption.
Sociology
Keywords: capitalism; commodity chains; consumption (economics); double movement; environmental degradation; industries; pollution

A contribuição de Karl Polanyi para a sociologia do desenvolvimento rural - Schneider, Sergio; Escher, Fabiano (Sociologias, 2011)
O ensaio aborda a importância da redescoberta do pensamento de Karl Polanyi e de sua crítica à "sociedade de mercado" na retomada dos estudos e debates sobre o desenvolvimento (rural). Após uma apresentação geral do quadro teórico e analítico de Polanyi, buscamos utilizar seus conceitos para interpretar a dinâmica da mercantilização dos meios de vida e das formas sociais de trabalho e produção no espaço rural, bem como dos sistemas agroalimentares no capitalismo contemporâneo. Com base nestas proposições, refletimos sobre o papel dos atores sociais e das instituições nos processos de mudança social em geral e os de desenvolvimento rural em particular. Finalizamos, propondo algumas potencialidades dessa abordagem para os estudos sobre desenvolvimento rural no Brasil. ENG: The essay deals with the importance of the rediscovery of Karl Polanyi's thinking and of his criticism of the "market society" in resuming (rural) development studies and debates. Following an overall presentation of Polanyi's theoretical and analytical framework, we look for using his concepts to interpret the commoditization dynamics of the rural livelihoods and the social forms of labor and production in the rural space, as well as the commoditization of the agri-food systems in the contemporary capitalism. Based on these statements, we reflect about the role of social actors and institutions in the processes of social change at large and of rural development in particular. And, finally, we propose some potentialities of this approach for the rural development studies in Brazil.
Sociology; Economics
Keywords: commoditization; institutions; rural development; social actors

Market Society or Society of Marketness? An Analysis Based on the Controversy between Karl Polanyi and Douglass North–《Sociological Studies》2011年04期 - Yonghua, Liu (2011)
Karl Polanyi and Douglass North hold totally opposite views on the understanding of the industrial revolution.The former analyses the formation of market society within the framework of mutual benefit,reallocation and market analysis,while the latter is interested in the essential importance of transaction cost and institutional transition to the industrial revolution.This paper attempts to rediscover the implication of modern society and the sense of freedom which is closely related to it by illuminating these two scholars' understandings.
Sociology
Keywords: NORTH; Douglass; industrial revolution; market society